2018
DOI: 10.1016/j.heliyon.2018.e00682
|View full text |Cite|
|
Sign up to set email alerts
|

Removal of chromium (VI) from aqueous solution using vesicular basalt: A potential low cost wastewater treatment system

Abstract: In this study, vesicular basalt volcanic rock was taken and its application for adsorption of chromium (VI) from aqueous solution was investigated. Different physical and chemical properties of the powdered rock was studied using Fourier transform infrared spectroscopy (FT-IR), Powder X-ray diffraction (XRD) and scanning electron microscopy (SEM). A series of batch experiments were carried out to study the effect of various experimental parameters (pH, ionic strength and contact time) on chromium (VI) adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Therefore, equilibrium was achieved at the 420 min contact time. Similar materials were used to remove chromium from the aqueous solution, and adsorption equilibrium was attained at 540 min [ 38 ]. However, a fast equilibrium time was attained at 120 min for blended rock materials with chitosan, used to remove arsenic from aqueous solution [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, equilibrium was achieved at the 420 min contact time. Similar materials were used to remove chromium from the aqueous solution, and adsorption equilibrium was attained at 540 min [ 38 ]. However, a fast equilibrium time was attained at 120 min for blended rock materials with chitosan, used to remove arsenic from aqueous solution [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to their vascular structure, high contents of silica, alumina, iron oxides and alkaline earth metals, large surface areas, and environmental friendliness, VPum and VSco are given conspicuous roles for pollutants removal (i.e., phosphate ions) [ 16 , 35 ]. Previous studies have showed the adsorption efficiency of volcanic rocks (pumice and scoria) with heavy metals [ 36 , 37 , 38 , 39 ], fluoride [ 40 ], and phosphorus [ 41 ] in a single system. In Ethiopia, volcanic rocks are also applied to remove hazardous pollutants from tannery wastewater [ 39 ], but there is little information on which raw volcanic rocks have been applied to remove phosphate from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…HCrO 4 and Cr 2 O 7 2predominantly exist at solution pH within the range of 2.0-6.0. It is also established that HCrO 4 is the dominant form of Cr(VI) at pH 2.0 [33]. Raising pH shifts the concentration of HCrO 4 to other forms, Cr 2 O 7 2and CrO 4 2-.…”
Section: Influence Of Phmentioning
confidence: 97%
“…Unlike in chemical treatment, biosorbents contain a vast number of organic compounds with many different types of functionalities which would attract heavy metal ions through complexation, in addition to other modes of mass transfer, such as ion exchange, transfer to micro-or macropores, and interparticle diffusion (Barakat 2011). Adsorption behavior of chromium on Muthurajawela peat (Priyantha et al 2015), vesicular basalt (Alemu et al 2018), fired brick particles (Priyantha and Seneviratne 2007), peel of jackfruit (Ranasinghe et al 2018), palm kernel fiber, and coconut husk (Ju and Ezuma 2014) has been investigated. Organic biosorbents have more advantages, such as low cost, high efficiency, minimum chemical use, low processing conditions, low energy technology, and high metal recovery (Richards et al 2019) as compared to synthetic materials,.…”
Section: Introductionmentioning
confidence: 99%